The Correlation Between Interest In Entrepreneurship And Students’ Self-Esteem - Mohamad Rizal Pautina; Meiske Puluhulawa; Moh. Rizki Djibran (Fakultas Ekonomi, Universitas Negeri Jakarta, 2018)
These days, unemployed workforces come from various backgrounds of education. Based on the data of Statistical Central Bureau, out of 133,94 million of the workforce, 6,87 million are unemployed. It is due to many individuals who only wait for job vacancy offered by either government or private institution. They do not have any willingness to create their own enterprise. A way to create a job is by entrepreneurship.